APPLICATION OF AUTOMATA THEORY TO DYNAMICAL CALCULATION OF MESHES AND MEMBRANES - Raspopov, O. S. (Science and Transport Progress, 2010)
The possibilities of application of the terminal automatic devices and associated matrices to modeling the grid and membrane vibrations with continuous mass distribution and different boundary conditions are examined